Optimization of termite in-ground monitoring stations: An evaluation trial - Sónia Duarte; Adam M. Taylor; Jeff D. Lloyd; Marta Duarte; Lina Nunes (Maderas: Ciencia y Tecnología, 2016)
Subterranean termites are serious pests of wood in service in much of the world. One of the most popular techniques for monitoring and controlling termites is the use of in-ground monitoring stations. Different cellulosic matrices were evaluated in terms of mass loss, moisture content variation and termite presence, accounting for spatial coordinates and monitoring station conditional variables, including: type of cellulosic matrix, matrix treatment and meteorological conditions, during one year in field conditions, both in Portugal and in the USA. A multivariate redundancy analysis was performed resulting in 60.4% of data variability being explained by the variables considered in this analysis. Spatial variables were responsible for the highest amount of variance observed in the response variables monitored for the termite monitoring stations, followed by the type of cellulosic matrix, from which cellulose and Hevea brasiliensis were the most influential variables. The optimization of termite in-ground monitoring stations should be performed through correct evaluation of termite feeding preferences and decay resistance, in order to choose an adequate bait matrix and a proper bait design. The termite species biology and the geographical location where control programs will be applied should also be taken into account.